Fungal isolates from marine sponge Chelonaplysilla sp.: Diversity, antimicrobial and cytotoxic activities - Dian Handayani; MUH. ADE ARTASASTA; NILDA SAFIRNA; DIANA FITRI AYUNI; TRINA EKAWATI TALLEI; TRIANA HERTIANI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Handayani D, Artasasta MA, Safira N, Ayuni DF, Tallei TE, Hertiani T. 2020. Fungal isolates from marine sponge Chelonaplysilla sp.: Diversity, antimicrobial and cytotoxic activities. Biodiversitas 21: 1954-1960. The purpose of this research was to study the diversity of fungi associated with marine sponges Chelonaplysilla sp. and their bioactivities. Fungal isolation was carried out by the multilevel dilution method in Saboraud Dextrose Agar (SDA). Twelve fungal isolates were successfully purified, then cultivated using rice for 4-6 weeks at room temperature and subsequently extracted using ethyl acetate. Antimicrobial activities of the fungal extracts were tested against Staphylococcus aureus, Escherichia coli, and Candida albicans by using the agar diffusion method. The extracts of isolates Ch05 and Ch12 showed a significant antagonistic effect against S. aureus and E. coli with the diameter that ranged from 15 to 17 mm. Using the brine shrimp lethality test (BSLT), six fungal extracts revealed cytotoxic activity with LC50 <100 µg/mL. Isolate Ch10 was the most potential fungus with the strong cytotoxic activity of LC50 of 0.90 µg/mL. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was conducted also for six potential fungal extracts against breast cancer cell (T47D). The isolate Ch05 showed moderate cytotoxic activity with IC50 of 83.69 µg/mL. The molecular identification was carried out for potential fungi using the ITS marker. The results showed that Ch02 was Aspergillus oryzae, Ch05 was Phomompsis sp., Ch06 was Penicillium simplicissimum, Ch10 was B. bassiana and Ch12 was Aspergillus mellinus. This study concluded that fungal isolates from marine sponge Chelonaplysilla sp. can be explored further for new sources of antimicrobial and anticancer compounds.